Should endovascular therapy be recommended for descending thoracic aortic dissections?. (December 2013) - Arafat, Amr; Idrees, Jahanzaib; Roselli, Eric E
Optimal therapy for descending aortic dissection is still a matter of controversy. Current recommendations are to treat uncomplicated dissections medically while preserving surgical interventions for complicated dissections. Thoracic endovascular aortic repair (TEVAR) has more recently been added to the armamentarium of treatment options for descending aortic dissection with the advantages of being a less invasive and potentially lower risk procedure. Several studies have compared TEVAR with other treatment modalities for acute and chronic indications; few of these are randomized studies. There is proven efficacy of TEVAR for acute complicated dissection, while experience with this treatment is growing for patients with chronic and uncomplicated dissection. This article will address the current role of TEVAR in treating descending thoracic dissection and provide a perspective on its future use.